2008
DOI: 10.1103/physrevb.77.014302
|View full text |Cite
|
Sign up to set email alerts
|

Dilution and clustering of Fe in the rutile phases ofTiO2andSnO2

Abstract: Dilute magnetic semiconductors of Fe-doped SnO 2 and TiO 2 with the structure of rutile were prepared in forms of powder and thin films using the techniques of sol gel and pulsed-laser deposition. We present the results of measurement of vibrational density of states of Fe impurity dopants in these oxides and demonstrate the cases of dilution and clustering. The oxygen pressure during the film deposition was varied between 10 −1 and 10 −8 Torr. In TiO 2 films made at 10 −1 Torr, Fe is diluted, however, in film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 53 publications
(72 reference statements)
1
14
0
Order By: Relevance
“…Recently, we have measured nuclear resonant inelastic scattering (NIS) spectra of metal oxides using synchrotron radiation, and revealed that NIS measurement is useful for determination of dilution or cluster formation of doped ions [3]. We also have conducted 119 Sn Mössbauer study of Fe doped SnO 2 under magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have measured nuclear resonant inelastic scattering (NIS) spectra of metal oxides using synchrotron radiation, and revealed that NIS measurement is useful for determination of dilution or cluster formation of doped ions [3]. We also have conducted 119 Sn Mössbauer study of Fe doped SnO 2 under magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Oxide diluted magnetic semiconductors, ODMS, in which nonmagnetic oxide semiconductors are doped with just a low percent of transition metal ions are expected to play an important role in the development of semiconductor spintronics [1,2]. Transition metal doped SnO 2 belong to these classes of materials [3][4][5]. Several synthetic methods to produce them have been explored, but many methods have the drawback of producing impurity phases and/or magnetic ion clustering.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] We have reported different types of magnetic source in case of Fe doped SnO 2 powders, prepared by sol-gel method and post annealing 3 , and also the phonon density of states (DOS) of rutile type structures of SnO 2 and TiO 2 . 4 The dilution and clustering of doping Fe species can be estimated by Mössbauer spectra and phonon DOS. We have clarified that the diluted Fe species probe the phonon DOS in SnO 2 more faithfully than in TiO 2 .…”
Section: Introductionmentioning
confidence: 99%